Hydrolysis of cassava cell walls through alkaline treatment and fermentation with alkaliphilic bacteria - Taylor, J.R.N. (John Reginald Nuttall) (University of Pretoria, 2018)
Thesis (PhD)--University of Pretoria, 2017.